The Values of Kediri Local Wisdom in the Qiroah Mahaliyah Text of Malzamah Arabiyah Book in the Syarqi Awwal Program at Markaz Arabiyah: (Critical Discourse Analysis Study Using Norman Fairclough's Model) - Miqdarul Khoir Syarofit; Salma, Ria Fauziah; Hanik Mahliatussikah; Abushihab, Eiman Fowzan (Asalibuna, 2025)
This research aims to identify and analyze the values of Kediri's local wisdom integrated in the Qiroah Mahaliyah texts of the Malzamah Arabiyah book used in the Syarqi Awwal Program at Markaz Arabiyah. Using Norman Fairclough's Critical Discourse Analysis approach, which emphasizes three analytical dimensions (text, discursive practice, and sociocultural practice), this study explores how local wisdom is represented, interpreted, and positioned in Arabic language teaching materials. The research corpus consists of nine reading texts in the Malzamah Arabiyah book containing Kediri's local wisdom content, including historical figures, cultural monuments, traditional cuisine, tourist attractions, and educational institutions. The results show that: (1) textually, there is a strong representation of Kediri's cultural identity and history through the use of lexicon, grammar, and text structures deliberately designed to highlight local excellence; (2) in the dimension of discursive practice, this book interprets local wisdom as an instrument of language-culture integration that functions to facilitate Arabic language learning through contexts familiar to learners; and (3) from the sociocultural aspect, the texts reproduce Islamic values that harmonize with local culture, strengthening the narrative of moderate Islam that forms the identity of Markaz Arabiyah. This research also reveals ideological agendas in the form of strengthening Islamic identity, reinforcing sociocultural bonds with local communities, cultural preservation, and introducing multicultural values through language learning. These findings contribute to the development of Arabic language learning models based on local wisdom that are contextual, meaningful, and in continuity with the cultural identity of learners.